Direct and indirect costs in Islamic finance – opportunities for research - Mustaffa Kamil, Nazrol Kamil (2019)
This is an exploratory conceptual paper that attempts to highlight some potential research areas related to the aspects of direct and indirect costs in Islamic finance. Questions on whether indirect costs should be included in compensation calculation and in computing mudarabah profit, as well as the issue for indirect costs in the context of Islamic banking windows, are deliberated upon. The paper articulates a comparison of costs of Islamic banks vis-à-vis conventional banks in terms of cost of funds, general cost efficiencies, regulatory costs, asset-liability management and risk management costs, operational costs and costs of bad debt. The risk of non-Shari’ah compliance and how it may impact costs are also highlighted. Finally, the paper briefly discusses some cost aspects relevant to Islamic capital markets.